Light Management With Grating Structures in Optoelectronic Devices - Wang, Wei; Wang, Gong; Zhang, Yang; Sun, Xiang-Chao; Yu, Yu; Lian, Yudong (Frontiers in Chemistry, 2021)
Ordered and patterned micro/nanostructure arrays have emerged as powerful platforms for optoelectronic devices due to their unique ordered-dependent optical properties. Among various structures, grating structure is widely applied because of its simple fabrication process, easy adjusting of size and morph, and efficient light trapping. Herein, we summarized recent developments of light management with grating structures in optoelectronic devices. Typical mechanisms about the grating structures in optoelectronic devices have been reviewed. Moreover, the applications of grating structures in various optoelectronic devices have been presented. Meanwhile, the remaining bottlenecks and perspectives for future development have been discussed.